WhatsApp Status, Social Uses, and Digital Vulnerabilities: A Critical Plea on Self-Exposure in the Congolese Context - Grevisse, Yende Raphaël (PT. Teknologi Futuristik Indonesia, 2026)
The rapid expansion of digital communication platforms has transformed everyday social interactions in many African societies, including the Democratic Republic of Congo (DRC). Among these platforms, WhatsApp occupies a central position, particularly through its Status feature, which allows users to share short-lived messages, images, and videos with their contacts. Despite its popularity, the social implications and digital security risks associated with this feature remain insufficiently studied in the Congolese context. This study addresses this research gap by examining the social uses of WhatsApp Status and their relationship with digital vulnerability. Using a qualitative analytical approach based on literature review and socio-digital observation, the research explores how everyday communication practices can unintentionally expose users to security risks. The findings reveal that limited understanding of privacy settings, normalized self-disclosure, and weak digital literacy significantly increase users’ vulnerability. Many individuals share financial, professional, geographical, or emotional information without fully understanding the potential audience or the risks associated with data circulation. Consequently, WhatsApp Status becomes not only a space for social expression but also a potential source of opportunistic cybercrime through social engineering strategies. The study highlights the urgent need to strengthen digital literacy, promote responsible online behaviour, and develop clearer privacy mechanisms within digital platforms. Ultimately, improving digital awareness and governance in the DRC is essential to reduce vulnerabilities and encourage safer digital practices in rapidly evolving online environments.